Determinant Factors in Management of Sharia-Based Hotels in Makassar City - Muhammad Yusuf (PINISI Discretion Review, 2022)
This study aims to determine the determinants of sharia-based hotel management in Makassar City. This study used a qualitative approach with a descriptive research type. The data sources in this study are hotels in the city of Makassar that have implemented sharia. The hotels in question are: (1) Al Badar Hotel, (2) Pesonna Hotel Makassar, and (3) JL Star Hotel. The subjects of this study are the managers including: (1) managers/managers and (2) hotel employees. While the research informants were (1) hotel visitors, and (2) the Indonesian Ulema Council (MUI) of South Sulawesi Province. The results of the study reveal that sharia-based hotel management in Makassar has not been fully implemented as a pure sharia-based hotel, only carrying out and running hotels with the concept of sharia-based hotels from the name side. So it can be said that de jure cannot be said to be a sharia-based hotel. Meanwhile, in terms of implementing sharia-based hotels in the city of Makassar, the determining factor is the strong will of managers to implement the concept of sharia-based hotels. Therefore, sharia-based hotel management as required by the DSN-MUI Fatwa No. 108 of 2016, the most important thing as an absolute requirement is that the preparation of the hotel organizational structure must be carried out immediately by incorporating the "Sharia Council" element into the organizational structure.